Implementation Of Healthcare Waqf: A Case Study Of Universiti Sains Islam Malaysia's Specialist Health Clinic - Wan Abdul Fattah Wan Ismail; Johari, F; Baharuddin, AS; Ahmad, MH; Alias, MH (IIUM PRESS, 2024)
Indexed by WOS